Investigation of archaeological amphorae from the Egadi battles. Issue 1 (1st April 2022) - Armetta, Francesco; Ciaramitaro, Veronica; Sójka, Małgorzata; Saladino, Maria Luisa; Zych, Eugeniusz
Abstract: Archaeological ceramics are considered one of the most important sources of both technological and chronological information. Here, the investigation of some archaeological underwater amphorae from the Egadi's Battle, that decided the end of the First Punic War (241 B.C.), is reported. X-ray Diffraction (XRD), X-ray Fluorescence (XRF), petrography, and Thermoluminescence (TL) were used to determine the composition of the amphorae and to evaluate the compatibly of their age with the above Battle. Considering the historical importance of the act and the well-defined historical collocation these amphorae represent an interesting archaeometric case study.